BEYOND WORDS: THE ROLE OF PARALINGUISTICS IN EFFECTIVE COMMUNICATION - Mamurova, Shakhlo (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
Effective communication goes beyond just the words spoken; it involves various non-verbal elements, among which paralinguistics plays a critical role. Paralinguistics refers to the vocal elements accompanying speech that convey emotional nuance and intention, such as tone, pitch, rate of speech, volume, and pauses. This study investigates the impact of paralinguistic features on communication, highlighting how these vocal cues influence the emotional tone, clarity, and overall message reception. Utilizing both qualitative and quantitative research methods, the study explores cultural variations in the interpretation of these cues and their importance in cross-cultural communication. The findings emphasize that paralinguistic cues, when interpreted correctly, can enhance understanding and reduce the potential for miscommunication, particularly in globalized and multicultural settings.